2018
DOI: 10.1371/journal.pcbi.1006024
|View full text |Cite|
|
Sign up to set email alerts
|

Free energy profiles for unwrapping the outer superhelical turn of nucleosomal DNA

Abstract: The eukaryotic genome is packaged into a nucleus in the form of chromatin. The fundamental structural unit of chromatin is a protein-DNA complex, the nucleosome, where 146 or 147 base pairs of DNA wrap 1.75 times around a histone core. To function in cellular processes, however, nucleosomal DNA must be unwrapped. Although this unwrapping has been experimentally investigated, details of the process at an atomic level are not yet well understood. Here, we used molecular dynamics simulation with an enhanced sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 68 publications
5
28
0
Order By: Relevance
“…Furthermore, we showed a free energy profile for unwrapping DNA from the canonical nucleosome. The profile suggested that a free energy for unwrapping the outer superhelical turn is about 11.5 kcal/mol which agrees well with values obtained in single molecule experiments [20]. The detailed analysis showed that asymmetric unwrapping of DNA is dominant, i.e., either end of DNA firstly unwraps from the histone core by up to 10 bps, then the other end of DNA starts to unwrap.…”
Section: Umbrella Sampling and Free-energy Profile Using Whamsupporting
confidence: 84%
See 4 more Smart Citations
“…Furthermore, we showed a free energy profile for unwrapping DNA from the canonical nucleosome. The profile suggested that a free energy for unwrapping the outer superhelical turn is about 11.5 kcal/mol which agrees well with values obtained in single molecule experiments [20]. The detailed analysis showed that asymmetric unwrapping of DNA is dominant, i.e., either end of DNA firstly unwraps from the histone core by up to 10 bps, then the other end of DNA starts to unwrap.…”
Section: Umbrella Sampling and Free-energy Profile Using Whamsupporting
confidence: 84%
“…This differs from the canonical NCP where asymmetric unwrapping conformations were dominantly observed (see Fig. 6 in a reference [20]).…”
Section: Comparison With the Canonical Ncpmentioning
confidence: 63%
See 3 more Smart Citations